Ecological integrity of Pasonaca Natural Park the sustainability of water supply under a policy of protected areas - Casimiro, Jessica Ma. Paz S.; Ramos, Ma. Sheila K. (2016)
This study establishes the optimum thresholds and rating scales to evaluate the ecological integrity of Pasonaca Natural Park protected area in Zamboanga City, Philippines. Six indicators representing four key eco-hydrological attributes of sustainable water supply namely vegetation and soil at the riparian buffer zone, the hydrology and water quality of the stream, were assessed. Tree basal area was found to be high ranging from 56.08 m2 ha-1 to 65.46 m2 ha-1 in undisturbed sites. These values are higher than other tropical forests in Southeast Asia. Total organic carbon and total nitrogen were at critical levels. Mean streamflow was significantly declining at 0.101 m3s-1yr-1 (p<0.001) suggesting the possibility of diminishing water supply in the coming years. The annual mean water turbidity was significantly increasing at 2.572 NTU yr-1 or 22.48% yr-1 (p<001) hinting at higher frequency of chemical treatment and increasing risk of exposure to disinfection by-products in drinking water. Annual high turbidity day account occured more than 90 days from 2007 to 2013 with the highest at 181 days in 2011. The overall ecological integrity rating of Pasonaca Natural Park is poor. The withdrawal of the riparian buffer zone from strict protection status and its reclassification to special use zone to pave the way for active management should be considered.
Keywords: Water resources